2002
DOI: 10.1074/jbc.m206911200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Nrf2 at Ser-40 by Protein Kinase C Regulates Antioxidant Response Element-mediated Transcription

Abstract: Nrf2, a basic leucine zipper transcription factor, is an essential activator of the coordinated transcription of genes encoding antioxidant enzymes and phase II detoxifying enzymes through the regulatory sequence termed antioxidant response element (ARE). Recently we reported evidence for the involvement of protein kinase C (PKC) in phosphorylating Nrf2 and triggering its nuclear translocation in response to oxidative stress. We show here that phosphorylation of purified rat Nrf2 by the catalytic subunit of PK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
660
1
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 937 publications
(695 citation statements)
references
References 37 publications
31
660
1
3
Order By: Relevance
“…Protein kinase C phosphorylates Nrf2 at Ser40, leading to Nrf2 dissociation from its endogenous inhibitor Kelch-like ECH associated protein 1 (Keap1), which results in nuclear translocation of Nrf2 in response to oxidative stress [54]. Therefore, we measured the levels of p-(Ser40)-Nrf2/Nrf2 in both cellular and nuclear extracts of striatal cells.…”
Section: Insulin and Igf-1 Enhance Phosphorylated Nrf2 Nuclear Levelsmentioning
confidence: 99%
“…Protein kinase C phosphorylates Nrf2 at Ser40, leading to Nrf2 dissociation from its endogenous inhibitor Kelch-like ECH associated protein 1 (Keap1), which results in nuclear translocation of Nrf2 in response to oxidative stress [54]. Therefore, we measured the levels of p-(Ser40)-Nrf2/Nrf2 in both cellular and nuclear extracts of striatal cells.…”
Section: Insulin and Igf-1 Enhance Phosphorylated Nrf2 Nuclear Levelsmentioning
confidence: 99%
“…It has been reported that the serine 40 residue (S40) of Nrf2, which is within the CD4 sequence, was phosphorylated by protein kinase C; phosphorylation at S40 was inducible by tBHQ and was necessary for the dissociation of Nrf2 from Keap1 and for the transcription activation activity of Nrf2 in a reporter assay in HepG2 cells [18,19]. We thus tested whether phosphorylation of S40 contributes to the slower migrating form of Nrf2.…”
Section: Identification Of the Transcription Activation Domain Of Nrfmentioning
confidence: 99%
“…Experiments employing specific inhibitors of the kinases implicated protein phosphorylation/dephosphorylation in the activation of Nrf2 [18,19]. However, due to the lack of direct biochemical evidence of phosphorylation of the Nrf2 protein, the role and mechanism of phosphorylation in Nrf2 regulation remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…1 Transcriptional activation through ARE is mainly regulated by NF-E2-related factor 2 (Nrf2), a member of Cap'n'Collar (CNC) family of transcription factors that share a highly conserved basic region-leucine zipper (bZIP) structure. 2 Nrf2 is abundantly expressed in liver, intestine, lung and kidney, where detoxification reactions occur routinely. Recently, Nrf2 and its downstream proteins have been shown to be critically important regulators in protection of cells from oxidative stress-and chemicalinduced damages of liver and lung tissues.…”
Section: Introductionmentioning
confidence: 99%